SINERGI CANVA DAN WORDWALL DALAM PEMBELAJARAN DIGITAL GENERASI Z DI SMA NEGERI 11 BANDA ACEH - Emalfida, Emalfida (Fitrah, 2023)
This study aims to optimize digital learning for Generation Z students at SMA Negeri 11 Banda Aceh through the synergistic use of Canva and Wordwall, focusing on the issues of student engagement and motivation in the current digital learning process. The research employs a Research and Development (R&D) methodology using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), conducted during the odd semester of the 2022/2023 academic year with a sample of 30 students selected through purposive sampling. The research instruments include learning outcome tests and questionnaires regarding the use of Canva and Wordwall. The analysis reveals a significant improvement from the pre-test (mean score of 44.3) to the post-test (mean score of 85.1), with an average N-Gain of 0.73, indicating that 73.3% of students fall into the high category. The t-test results show a t-value of 48.256 and a p-value of 0.000, confirming the significance of this improvement. Students' responses to digital learning were overwhelmingly positive, with ratings of "Very Good" and "Good" across various aspects, including learning experience, engagement, and effectiveness. The conclusion of this study indicates that the implemented digital learning model is effective in enhancing students' understanding and engagement.